Dimensionless load separation theory using SE(B) specimen and Software development - Kaikai Shi; Lixun Cai; Chen Bao; Yao Yao (Institute of Advanced Engineering and Science, 2012)
There is an unbalanced dimension problem in the existing load separation theory. According to the similar dimensionless theory, this article has obtained the dimensionless load separation theory. It finds out the modified Spb method which can be used to get the J integral resistance curve of ductile materials, which based on the dimensionless load separation theory. At the same time, the original testing software has advanced based on the modified theory in the process of getting fracture toughness of ductile material. The testing software is called J-LSS (J integral-the load separation software). Ultimately, this article provides the J integral resistance curve of pressure vessel material A508-3 steel using the J-LSS. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1694